Induction of a Major Leaf Acid Phosphatase Does Not Confer Adaptation to Low Phosphorus Availability in Common Bean - Yan, Xiaolong (American Society of Plant Physiologists, 2001)
Acid phosphatase is believed to be important for phosphorus scavenging and remobilization in plants, but its role in plant adaptation to low phosphorus availability has not been critically evaluated. To address this issue, we compared acid phosphatase activity (APA) in leaves of common bean (Phaseolus vulgaris) in a phosphorus-inefficient genotype (DOR364), a phosphorus-efficient genotype (G19833), and their F(5.10) recombinant inbred lines (RILs). Phosphorus deficiency substantially increased leaf APA, but APA was much higher and more responsive to phosphorus availability in DOR364 than in G19833. Leaf APA segregated in the RILs, with two discrete groups having either high (mean = 1.71 μmol/mg protein/min) or low (0.36 μmol/mg protein/min) activity. A chi-square test indicated that the observed difference might be controlled by a single gene. Non-denaturing protein electrophoresis revealed that there are four visible isoforms responsible for total APA in common bean, and that the difference in APA between contrasting genotypes could be attributed to the existence of a single major isoform. Qualitative mapping of the APA trait and quantitative trait loci analysis with molecular markers indicated that a major gene contributing to APA is located on linkage group B03 of the unified common bean map. This locus was not associated with loci conferring phosphorus acquisition efficiency or phosphorus use efficiency. RILs contrasting for APA had similar phosphorus pools in old and young leaves under phosphorus stress, arguing against a role for APA in phosphorus remobilization. Our results do not support a major role for leaf APA induction in regulating plant adaptation to phosphorus deficiency.